N-(4-Chlorophenyl)-3-nitropyridin-2-amine - Aznan, A.M.A.; Fairuz, Z.A.; Abdullah, Z.; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2011)
In the title compound, C(11)H(8)ClN(3)O(2), the presence of intramolecular N-H center dot center dot center dot O and C-H center dot center dot center dot N interactions help to establish an almost planar molecule [dihedral angle between the pyridine and benzene rings = 9.89 (8)degrees and r.m.s. deviation for all 17 non-H atoms = 0.120 angstrom]. Supramolecular tapes feature in the crystal packing whereby dimeric aggregates sustained by pairs of C-H center dot center dot center dot O interactions are connected by pi-pi interactions occurring between translationally related pyridine rings and between translationally related benzene rings along the b axis [centroid-centroid distance = length of b axis = 3.8032 (4) angstrom].